Therapeutic strategies for elbow ankylosis due to heterotopic ossification in patients with severe burns - Suito, Motomu (JPRAS Open, 2018)
BACKGROUND: Heterotopic ossification (HO) occurs frequently in the elbow in burn patients, and extends beyond the anatomical structure. HO of the elbow can cause joint contracture and adversely affect activities of daily living. Currently, there is no effective prophylaxis for HO as the precise underlying mechanism remains unknown. Therefore, there is no choice but to treat HO after it has developed. To date, however, no effective standard treatment has been reported, and therefore treatment methods vary between different facilities. Surgical resection is widely accepted as the only therapeutic option once HO limits functional mobility of the elbow. PURPOSES: Based on past reports, we examined our cases and recommend effective therapeutic strategies. We posed the following three questions: (1) Is the surgical intervention effective or detrimental for elbow ankylosis due to HO? (2) What is the best timing for the intervention? (3) What is the most effective postoperative rehabilitation plan? METHODS: We treated three patients with complete ankylosis of the elbow due to HO after severe burn injury using different protocols. RESULTS: Surgery was performed in two cases and rehabilitation therapy was commenced immediately from the first postoperative day. Both patients showed improvement in the active range of motion in their elbow joints. The other patient did not undergo surgery, and his elbows became fixed in the completely extension position. CONCLUSION: Surgical resection is beneficial for elbow ankylosis due to HO after burn injury. Although the exact surgical timing is still controversial, we recommend that surgery should be performed as soon as possible after improving the skin condition around the elbow and confirming the maturation of HO on radiographs. Early rehabilitation and pain control are also important after surgery.